Repeat dose NRPT (nicotinamide riboside and pterostilbene) increases NAD+ levels in humans safely and sustainably: a randomized, double-blind, placebo-controlled study. (December 2017) - Dellinger, Ryan; Santos, Santiago; Morris, Mark; Evans, Mal; Alminana, Dan; Guarente, Leonard; Marcotulli, Eric
Abstract NRPT is a combination of nicotinamide riboside (NR), a nicotinamide adenine dinucleotide (NAD+) precursor vitamin found in milk, and pterostilbene (PT), a polyphenol found in blueberries. Here, we report this first-in-humans clinical trial designed to assess the safety and efficacy of a repeat dose of NRPT (commercially known as Basis). NRPT was evaluated in a randomized, double-blind, and placebo-controlled study in a population of 120 healthy adults between the ages of 60 and 80 years. The study consisted of three treatment arms: placebo, recommended dose of NRPT (NRPT 1X), and double dose of NRPT (NRPT 2X). All subjects took their blinded supplement daily for eight weeks. Analysis of NAD+ in whole blood demonstrated that NRPT significantly increases the concentration of NAD+ in a dose-dependent manner. NAD+ levels increased by approximately 40% in the NRPT 1X group and approximately 90% in the NRPT 2X group after 4 weeks as compared to placebo and baseline. Furthermore, this significant increase in NAD+ levels was sustained throughout the entire 8-week trial. NAD+ levels did not increase for the placebo group during the trial. No serious adverse events were reported in this study. This study shows that a repeat dose of NRPT is a safe and effective way to increase NAD+ levels sustainably. Natural compounds restore NAD+ levels in humans It's possible to boost declining levels of NAD+, a molecule required for fundamental chemical reactions in the human body, with a dietary supplement. A team led by Leonard Guarente of MIT and Elysium Health gave 120 healthy adult volunteers between the ages of 60 and 80 NRPT (known commercially as Basis) over the course of eight weeks. Volunteers taking the regular dose of NRPT had 40 percent more NAD+ compared to their baseline when tested at four weeks and at eight weeks. Others who took a double dose of NRPT had even higher levels of NAD+, while those who took the placebo saw no increase. Research shows that NAD+ levels decline in animals and humans with age. Boosting NAD+ in animals improves age-associated diseases, so researchers now want to understand whether humans, too, may benefit.